MENINGKATKAN KEMAMPUAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) MELALUI GERAK DAN LAGU PADA KELOMPOK A TK MARSUDI ASIH LARANGAN KOTA TANGERANG - Tri Wahyuningtyah; Afifah Afifah; Nyayu Yayu Suryani (Jurnal Anak Bangsa, 2023)
The transition from the Covid 19 pandemic to a new normal life is an early routine for early childhood education. Clean and healthy living habits need to be formed from the age of kindergarten (TK). The purpose of this study was to determine the ability to implement clean and healthy living behaviors in group A children at Marsudi Asih Larangan Kindergarten, Tangerang City through the method of movement and singing. This research is classroom action research conducted in collaboration with colleagues through hands-on approaches and narrative analysis. The research data was collected from observation and reflection which was carried out through simulations of learning improvement results for two cycles. The cycle includes several stages such as: planning, implementing, observing and reflecting. The results of the Enhanced Learning simulation show that there are weaknesses and strengths in the Enhanced Learning simulation. The weakness lies in the teacher's technique in learning activities. The benefits are kid-friendly methods that make kids happy, creative, and productive. The method of moving through songs is proven to be able to improve children's ability to understand and demonstrate clean and healthy living behaviors: 69% developed as expected, 4% developed very well, so that initially the growth was only 13%. as expected